Peranan mikrobiologi dalam pengelolaan Lingkungan (Studi tentang mikro organisme di lingkungan alamiah) - Badrus, Susi Susilawati; Audia, Mia; Agustin , Nabila Rachel (Jurnal Sains dan Teknologi (JSIT), 2023)
Microbes are everywhere around us, some inhabiting the soil, water and atmosphere. The study of microbes in their natural environment is called microbial ecology. Ecology is a part of biology that is concerned with the study of the relationship of organisms or groups of organisms with their environment. Microbial ecology plays an important role in helping improve environmental quality. For example, microbes decompose waste from humans and industry that is thrown into it. A microorganism can grow well if the surrounding environmental conditions are very supportive. Microorganisms that grow are an increase in the number of microbes so that they can form a microbial population which can be called a colony and not cells that increase in size or length. The population of microorganisms can become very large in a relatively short period of time and the growth of microorganisms cannot be controlled. The presence of microorganisms in the environment can provide advantages and disadvantage